A cultural turn in urban governance: cultural practices of governance in the Guangdong-Hong Kong-Macau Greater Bay Area. Issue 2 (23rd February 2023) - Luo, Xianmei; Huang, Yurong
ABSTRACT: Tracing the concept and phenomena of 'cultural governance', as it evolves along the agenda of China's 'modernization of governing capacity (of the state)', this article tries to capture the various term-shaping processes against the backdrop of a political discourse that gave birth to them. The article discusses topics such as urban planning, infrastructure upgrading, community reformation, and the so-called cultural-sustainable development strategy adopted by the Chinese authorities with selected cases from three mainland Chinese urban centers (Shenzhen, Foshan and Dongguan) of the Guangdong-Hong Kong-Macau Greater Bay Area. Pointing to both the flexibility and adaptability of the state's involvement, the research elaborates the models adopted by and problems associated with various pioneering programs initiated by municipalities as they carry out what might be called, arguably, a 'cultural turn' of urban governance.